2023
DOI: 10.1021/acsami.2c20701
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the MXene–Zinc Interfacial Structure toward a Highly Revisable Metal Anode of Zinc–Air Batteries

Abstract: Rechargeable aqueous Zn−air batteries have been regarded as one of the most promising systems for flexible energy storage devices due to their high specific energy, safety, and cost effectiveness. However, Zn metal anodes exposed to strong alkaline electrolytes suffer from several issues such as corrosion, dissolution, and passivation, resulting in extremely poor cycle reversibility. Motivated by this challenge, we herein strategically design an MXene/Zn metal anode interfacial structure with single/few-layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Such differences of cycling lifespan and voltage hysteresis between CNF and WCCNF separators demonstrate that the WCCNF can promote the uniform Zn nucleation and the reversible Zn plating/stripping on Zn anode. 37,38 Rate performances of Zn∥Zn cells were measured at various current densities from 0.5 to 5 mA•cm −2 . As shown in Figure 3c, the voltage hysteresis of the Zn∥Zn cell with CNF arises violent fluctuation when operated at the current density of 2.5 mA• cm −2 and short-circuits at the current density of 3.5 mA•cm −2 , indicating the poor stability of the Zn anode caused by the CNF separator especially at high current density.…”
Section: Resultsmentioning
confidence: 99%
“…Such differences of cycling lifespan and voltage hysteresis between CNF and WCCNF separators demonstrate that the WCCNF can promote the uniform Zn nucleation and the reversible Zn plating/stripping on Zn anode. 37,38 Rate performances of Zn∥Zn cells were measured at various current densities from 0.5 to 5 mA•cm −2 . As shown in Figure 3c, the voltage hysteresis of the Zn∥Zn cell with CNF arises violent fluctuation when operated at the current density of 2.5 mA• cm −2 and short-circuits at the current density of 3.5 mA•cm −2 , indicating the poor stability of the Zn anode caused by the CNF separator especially at high current density.…”
Section: Resultsmentioning
confidence: 99%
“…14−16 Among these, constructing an artificial interphase to suppress water decomposition and regulate Zn plating emerge as key strategies for enhancing the electrochemical properties of zinc-ion batteries, including ex situ and in situ coating approaches. 17 Building a protective layer by ex situ coating inorganics (e.g., TiO 2 , 18 CaCO 3 , 19 graphene, 20 Ag, 21 Al 2 O 3 , 22 ZnF 2 , 23 HfO 2 , 24 Zn 3 (PO 4 ) 2 , 25 Si 26 ) or polymer [e.g., poly(vinyl butyral) (PVB), 5 poly(vinyl alcohol) (PVA), 27 T h i s c o n t e n t i s silk fibroin, 28 polyimide 29 ] on the surface of Zn anodes is an attractive method to regulate Zn dendrites by allowing Zn 2+ to transport but blocking water penetration to Zn surfaces. Nevertheless, this method usually requires binders and produces rough and thick coatings (>10 μm), which can increase the electrolyte−electrode interface resistance and reduce the energy density.…”
Section: ■ Introductionmentioning
confidence: 99%
“…21 Several studies have reported the development of a ZnO architecture coating on a Zn anode. 4,32,33 For instance, a three-dimensional nanoporous ZnO coating on a Zn plate was shown to enhance the kinetics of Zn 2+ transfer and deposition due to the electrostatic attraction effect resulting from the porous structure and inert ZnO interface. 4 Another study demonstrated that the application of a ZnO interface could suppress dendrite growth, which was attributed to the reduction in local current density achieved by enlarging the surface area with the ZnO coating.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this inspiration, various effective strategies dedicated to promoting uniform deposition of Li and Zn ions have been developed. , One particularly successful approach involves employing an anode protection layer. Recently, various protection layers such as organic polymers, organic–inorganic compounds, , and two-dimensional layered materials have been developed to effectively induce uniform Li or Zn ion deposition and thus extend the cycle life. However, the thicknesses of these conventional interfacial protection layers typically range from 5 to 100 μm, imposing limitations on the overall anode energy density.…”
mentioning
confidence: 99%